Implementation of classroom management by English teachers at high schools in Jambi, Indonesia - Akhmad Habibi; Amirul Mukminin; Muhammad Sofwan; Urip Sulistiyo (Studies in English Language and Education, 2017)
This study was aimed at analyzing the implementation, processes and problems of classroom management in two Indonesian high schools from the perspective of English teachers in accordance with the latest, 2013, Indonesian curriculum. The research was qualitative with a case study approach. The sites for this study were two national senior high schools in Jambi Province, Indonesia. Eight teachers of English were involved as the research participants to provide a broad perspective of implementation of classroom management. The researchers used four techniques for collecting data: interviews, focus group discussions, observations, and document review. To assess the trustworthiness of the research, the researchers did triangulation, member checking and reflexivity. The findings, describing the implementation, processes and problems of classroom management, are divided into three themes: (i) teaching standards, rules and procedures, (ii) classroom climate, and (iii) timing and scheduling. Policy recommendation proposed such as to limit the number of students (in a class), to provide up-to-date technology and to provide more training for teachers are not only for teachers but also for school authorities, and other stake holders for the betterment of Indonesian education.